Direito à moradia : desafios contemporâneos quanto à sua conceituação e concretização à luz do direito à cidade - Santos, Eloísa Assis dos (2021)
Inserted in the list of social rights, due to Constitutional Amendment nº 26, of 2000, the right to housing emerges as a fundamental right with a double dimension, since, although it corresponds to a subjective right to positive benefits, its negative nature is not ignored, which is made explicit above all in the prohibition of forced removals. The formal recognition of access to housing as a social right, however, does not translate into factual fulfillment of the protected legal property – a finding that demonstrates explaining the growing housing deficit in Brazilian cities. Remains the understanding that the right to housing is only made by promoting access to home ownership, a circumstance that reveals the distancing of the concept of housing as a right and a mistaken approach to understanding housing as a commodity. The Minha Casa Minha Vida Program (PMCMV), the most important housing program in Brazilian history, demonstrates the fragility of political action that is guided by the profitability, since the PMCMV reproduced inequalities by building housing complexes far from the urban center in reason of the low price of land, reinforcing territorial segregation. The challenges for the spread of the coronavírus – especially due to the finding of the numerous situations of cohabitation and excessive density, in addition to the lack of access to basic sanitation, since many families do not even have access to treated water and to toilets – reinforce the urgency to overcome the classic understanding of the right to housing, which, despite being constituted as an autonomous right, from the promulgation of the Estatuto da Cidade, must be understood as an interdependent right and included in the concept of right to the city, which, currently, it is outlined as a legal instrument to demand a dignified life in the urban space, and it is recognized that the urban perspective is an insupportable content of the – resignified – concept of the right to housing.